Enhancing Kefir with Raspberry Pomace: Storage-Dependent Changes in Quality and Stability - Sandra Stamenković Stojanović; Ljubica Živković; Jelena Stanojević; Bojana Danilović; Stojan Mančić; Ivana Karabegović (Fermentation)
This study evaluated the effects of raspberry pomace addition on kefir’s chemical, microbiological, and sensory properties during a 14-day refrigerated storage. Kefir samples were prepared using 10% and 20% raspberry pomace, either retaining or straining out pomace after fermentation. Raspberry pomace notably enhanced antioxidant activity, peaking at 95.91% DPPH radical reduction on day 10, and increased total polyphenol content to 78.24 mg gallic acid/L. Pomace addition also improved microbiological stability, maintaining higher lactic acid bacteria (7.48 log CFU/mL) and stable yeast counts. Repeated measures ANOVA revealed a significant effect of storage duration on the concentrations of all analyzed parameters. Results showed that pomace-enriched samples, particularly those retaining pomace during storage, exhibited significantly higher levels of lactic, acetic, and citric acids, as well as ethanol and residual sugars. Sensory evaluations revealed kefir samples with strained raspberry pomace had the highest consumer acceptability, scoring 7.8 out of 9 for overall acceptance due to balanced flavor and improved texture. These results highlight raspberry pomace’s potential as a valuable ingredient for improvement in kefir, offering a promising approach to functional dairy innovation.